Appearance of Multi-Nucleated Blastomeres of Human Embryos Following Cryorpeservation - Petrushko, M. P. (Problems of Cryobiology and Cryomedicine, 2004)
The frequency of multinucleated blastomere appearance in human embryos after cryopreservation from 2.1 to 8.2 % was shown to increase. There was demonstrated, that the nuclei rate in blastomeres correlated with its ploidy rate. Fusion of cell membranes or karyokinesis without cytokinesis is the possible mechanism of blastomere poliploidy.